Dynamic Effects of Microcredit in Bangladesh - Khandker, Shahidur R.; Samad, Hussain A. (World Bank, Washington, DC, 2014)
This paper uses long panel survey data spanning over 20 years to examine the dynamics of microcredit programs in Bangladesh. With the phenomenal growth of microfinance institutions representing 30 million members with over $2 billion of annual disbursement over the past two decades, it is important to understand the dynamics of microcredit expansion and its induced impact on household welfare. A dynamic panel model is used to address a number of issues, such as whether credit effects are declining over time, whether market saturation and village diseconomies are taking place, and whether multiple program membership, which is rising as a consequence of microcredit expansion, is harming or benefiting the borrowers. The paper's results confirm that microcredit programs have continued to benefit the poor by raising household welfare. The beneficial effects have also remained higher for female than male borrowers. There are diseconomies of scale caused by higher levels of village-level borrowing, especially for male members. Multiple program membership is also growing with competition from microfinance institutions, but this has rather helped raise assets and net worth more than it has contributed to indebtedness.